The prevalence of unsuspected onychomycosis and its causative organisms in a multicentre Canadian sample of 30 000 patients visiting physicians' offices. (11th May 2016) - Gupta, A.K.; Gupta, G.; Jain, H.C.; Lynde, C.W.; Foley, K.A.; Daigle, D.; Cooper, E.A.; Summerbell, R.C.
Abstract: Background: Onychomycosis is difficult to treat and a concern for many patients. Prevalence estimates of onychomycosis in North American clinic samples have been higher than what has been reported for general populations. Objective: A large, multicentre study was conducted to estimate the prevalence of toenail onychomycosis in the Canadian population. Methods: Patients were recruited from the offices of three dermatologists and one family physician in Ontario, Canada. Nail samples for mycological testing were obtained from normal and abnormal‐looking nails. This sample of 32 193 patients includes our previous published study of 15 000 patients. Results: Abnormal nails were observed in 4350 patients. Of these, the prevalence of culture‐confirmed toenail onychomycosis was estimated to be 6.7% (95% CI, 6.41–6.96%). Following sex and age adjustments for the general population, the estimated prevalence of toenail onychomycosis in Canada was 6.4% (95% CI, 6.12%–6.65%). The distribution of fungal organisms in culture‐confirmed onychomycosis was 71.9% dermatophytes, 20.4% non‐dermatophyte moulds and 7.6% yeasts. Toenail onychomycosis was four times more prevalent in those over the age of 60 years than below the age of 60 years. Conclusion: The present data highlights that onychomycosis may be a growing medical concern among ageing patients.